Airborne noise emissions from ships: Experimental characterization of the source and propagation over land. (March 2016) - Badino, Aglaia; Borelli, Davide; Gaggero, Tomaso; Rizzuto, Enrico; Schenone, Corrado
Abstract: In noise mapping of urban areas main sources for nuisance and sleep disturbance are roads, railways, airports and industrial plants. However, when a noise analysis of port cities is carried out, also harbor activities are to be considered as significant contributors to the 'soundscape'. Within the harbor, ships, when berthed at wharfs and possibly busy in loading or unloading operations, represent significant sources of noise. In these conditions, in fact, some of the ship's plants are running and high airborne noise levels may be radiated. Ships are not traditionally characterized as noise sources and their dimensions and complexity pose a challenge for the description of the acoustical field in urban areas around the port. The work presents a hybrid experimental–computational approach for the acoustical characterization of ships applied to a test case represented by a multipurpose ship. For the same ship, the propagation field is studied numerically to include an urban area around the port. The same experimental campaign is also used to introduce a new measurement procedure for an effective characterization of the ship source.